The effects of Mg2+ and Ba2+ dopants on the microstructure and magnetic properties of doubly-doped LaFeO3 perovskite catalytic nanocrystals. Issue 3 (15th February 2019) - Lin, Qing; Lin, Jinpei; Yang, Xingxing; He, Yun; Wang, Liping; Dong, Jianghui
Abstract: Using citrate sol-gel method, we prepared La0.85 Mg0.15- x Ba x FeO3 ( x  = 0.02–0.12) samples. X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and vibrating sample magnetometer (VSM) were used to investigate whether the microstructure, composition, and magnetic properties of LaFeO3 were affected by the following parameters: calcination temperature, calcination time, and the doping concentration of Mg 2+ ion and Ba 2+ ions. The XRD spectra showed that a trace of impurity phase (MgFe2 O4 ) is visible when the content of Mg 2+ ions was higher; however, there was no change in the orthorhombic perovskite structure of LaFeO3 even at higher doping concentrations. The space group was still Pnma . No other phase was generated in the sample subjected to low-temperature calcination. Furthermore, FT-IR spectra confirmed the presence of some functional groups in the sample. Then, SEM showed that the size distribution of the particles is uniform in the sample, and the grain boundary is also clear. Finally, VSM measurements proved that the significant changes were produced in the magnetic properties of samples when they were doubly doped with Mg 2+ and Ba 2+ ions. Moreover, calcination temperature has a great influence on the magnetic properties of the samples.